The correlation between passive and dynamic rotation in both the lead and trail hips of healthy young adult male golfers during a golf swing - Alderslade, Villene (Stellenbosch : Stellenbosch University, 2014)
Thesis (MScPhysio)--Stellenbosch University, 2014.